3*(5-2)+ 7*1

We will simplify the expression using the priorities of the operations.

The first priority is to the parenthesis.

==> 3*(5-2) + 7*1 = 3*3 + 7*1

Now the second priority is to the division and multiplication.

==> 3*3 + 7*1 = 9 + 7

Now the last thing we do is add or subtract.

==> 9 + 7 = 16

**Then, the answer is 16**

First, you have to do the part that is in the parenthesis. That gives you

3*3 + 7*1

Multiplication comes before addition. So now you have to multiply those numbers. That gives you

9 + 7

Now that you have done that, all you have left to do is add.

The first step is to do what is inside brackets:

5 - 2 = 3

Now, we'll substitute 3 for 5 - 2.

The next step is to start multiply from left to the right

3*3 + 7*1 = 9 + 7

Now, we'll add from left to right:

9 + 7 = 16

**The solution is 16.**